2021
DOI: 10.15700/saje.v41n2a1779
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the learning performance gap between urban and rural areas in sub-Saharan Africa

Abstract: The learning gap between urban and rural areas is a persistent problem in many sub-Saharan African countries. Previous studies have found that the urban-rural learning gap is attributed to the fact that student characteristics and school resources are different in urban and rural areas. Our study updates this finding by using the latest dataset and further examines the changes in the attributed sources over time. Using 15 educational systems in sub-Saharan Africa, we examined 4 potential sources of the gap: st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The educational systems in Africa were structurally fragile even before the pandemic, with unequal educational opportunities and infrastructure (including resources to pivot to remote learning during emergencies) for different socioeconomic groups [ 37 ]. Literacy and learning performance gaps between rural and urban settings in sub-Saharan Africa are documented prior to the COVID-19 pandemic [ 38 ]. It was unclear to what extent the rural-urban disparity was the additional impact of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The educational systems in Africa were structurally fragile even before the pandemic, with unequal educational opportunities and infrastructure (including resources to pivot to remote learning during emergencies) for different socioeconomic groups [ 37 ]. Literacy and learning performance gaps between rural and urban settings in sub-Saharan Africa are documented prior to the COVID-19 pandemic [ 38 ]. It was unclear to what extent the rural-urban disparity was the additional impact of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Another research reported that the academic performance of rural students was significantly worse than that of urban students. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Different studies confirm that secondary school students in Africa perform poorly in geography (Anlimachie, 2019;Eze, 2021;Mwesiga, 2017;Opoku, et al, 2020;Yahaya, et al, 2021). By comparing rural and urban schools, some studies found that students from rural schools perform better compared with their counterparts from urban schools (Nidup, 2022;Oyeromi, et al, 2018;) and this contradicted by others revealing that urban schools perform better than rural schools (Opoku-Asare & Siaw, 2015; Sumida & Kawata, 2021;Vishwajeet & Girish, 2018).…”
Section: Performance Of Geography Studentsmentioning
confidence: 98%